Protective role of ginger and curcumin against some toxicological effects induced by thermoxidized frying cotton oil - Hamoudah, Somaya Youssef Mostafa; Hassanin, Mahrousa Mohamed; Youssef, Gehan Ahmed (Comunicata Scientiae, 2010)
In Egypt, the bad economic situation in many homes often demand that oil previously fried is reused and this may constitute health risk to consumers. The aim of the present work was to investigate the protective role of ginger and curcumin powders against some toxicological effects of thermoxidized frying cotton oil (OFO). Thirty five male albino rats were divided into seven groups: negative control, ginger-treated group (1 g/100 g in diet), curcumin treated group (0.2 g/100 g diet), fresh cotton oil treated group (15 mL/kg orally), OFO – treated group (15 mL/kg orally), OFO (15 mL/kg orally) + ginger (1 g/100 g in diet) – treated group and OFO (15 mL/kg orally) + curcumin (0.2% in diet) – treated group. After 28 days of experiment, the results indicated that OFO treated group showed significant (p≤ 0.05) increase in both liver enzymes (AST and ALT) and glucose levels. Significant increase in the frequencies of chromosomal aberrations in somatic and germ cells were encountered. Histopathological changes in liver in form of fatty changes and central vein congestion were observed. The addition of ginger or curcumin to diet of OFO treated group produced improvement in the liver function, decrease in the glucose level, increase in the level of total antioxidants, reduction in the frequencies of chromosomal aberrations and improvement of the hepatic pathological changes. In conclusion, ginger and curcumin can protect against toxicity of frying oil, but, curcumin needs further investigation to find the effective and safe dose.